ESG Disclosure in Emerging Markets: Implications for Investment-Financing Maturity Mismatch in Non-Financial Firms Across ASEAN-4 (2019–2023) - Ummi Nurun Nissa; Nur Dhani Hendranastiti (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Purpose – This study aims to empirically investigate the effect of Environmental, Social, and Governance (ESG) disclosure on investment-financing maturity mismatch using a fixed effects panel regression method. Methodology – The sample consists of 76 publicly listed non-financial companies from developing countries in the ASEAN-4 region, Indonesia, Malaysia, Thailand, and the Philippines, during the period 2019–2023. Findings – The results show that higher overall ESG disclosure and governance disclosure scores are associated with a reduced risk of investment-financing maturity mismatch, while the environmental and social aspects do not have a significant effect. Additionally, the findings indicate that during the COVID-19 pandemic, companies became more cautious in managing financing risks and there are variations in maturity mismatch management among ASEAN-4 countries. Originality – This study focuses on the effect of sustainability disclosures on investment-financing maturity mismatch in non-financial firms across ASEAN-4, that has not been widely discussed.